Enhancing mTOR-targeted cancer therapy by preventing mTOR/raptor inhibition-initiated, mTOR/rictor-independent Akt activation - Wang, Xuerong (2008)
It has been shown that mTOR inhibitors activate Akt while inhibiting mTOR signaling. However, the underlying mechanisms and the impact of the Akt activation on mTOR-targeted cancer therapy are unclear. The present work focused on addressing the role of mTOR/rictor in mTOR inhibitor-induced Akt activation and the impact of sustained Akt activation on mTOR-targeted cancer therapy. Thus, we have demonstrated that mTOR inhibitors increase Akt phosphorylation through a mechanism independent of mTOR/rictor because the assembly of mTOR/rictor was inhibited by mTOR inhibitors and the silencing of rictor did not abrogate mTOR inhibitor-induced Akt activation. Moreover, Akt activation during mTOR inhibition is tightly associated with development of cell resistance to mTOR inhibitors. Accordingly, co-targeting mTOR and PI3K/Akt signaling prevents mTOR inhibition-initiated Akt activation and enhances antitumor effects both in cell cultures and in animal xenograft models, suggesting an effective cancer therapeutic strategy. Collectively, we conclude that inhibition of the mTOR/raptor complex initiates Akt activation independent of mTOR/rictor. As a result, the sustained Akt activation during mTOR inhibition will counteract mTOR inhibitors’ anticancer efficacy.